Characteristics, management and outcome of a large necrotising otitis externa case series: need for standardised case definition. Issue 7 (19th July 2022) - Hodgson, S H; Sinclair, V J; Arwyn-Jones, J; Oh, K; Nucken, K; Perenyei, M; Sivapathasingam, V; Martinez-Devesa, P; Pendlebury, S T; Ramsden, J D; Matthews, P C; Pretorius, P; et al.
Abstract: Background: Necrotising otitis externa is a severe ear infection for which there are no established diagnostic or treatment guidelines. Method: This study described clinical characteristics, management and outcomes for patients managed as necrotising otitis externa cases at a UK tertiary referral centre. Results: A total of 58 (63 per cent) patients were classified as definite necrotising otitis externa cases, 31 (34 per cent) as probable cases and 3 (3 per cent) as possible cases. Median duration of intravenous and oral antimicrobial therapy was 6.0 weeks (0.49–44.9 weeks). Six per cent of patients relapsed a median of 16.4 weeks (interquartile range, 23–121) after stopping antimicrobials. Twenty-eight per cent of cases had complex disease. These patients were older ( p = 0.042), had a longer duration of symptoms prior to imaging ( p < 0.0001) and higher C-reactive protein at diagnosis ( p = 0.005). Despite longer courses of intravenous antimicrobials (23 vs 14 days ; p = 0.032), complex cases were more likely to relapse ( p = 0.016). Conclusion: A standardised case-definition of necrotising otitis externa is needed to optimise diagnosis, management and research.